Esther in diaspora : toward an alternative interpretive framework - Mapfeka, Tsaurayi K., (Biblical Interpretation Series;, 2019)
In Esther in Diaspora, Tsaurayi Kudakwashe Mapfeka presents a new approach to the book of Esther in the Hebrew Bible. He argues that, whereas previous interpretations have emphasised an association with the Jewish festival of Purim, a theory-nuanced concept of diaspora offers the key for reading Esther. Alongside the relatively new approach of Diaspora Studies, the author makes use of the more traditional analogical reasoning, seeing parallels between the community behind Esther and the Zimbabwean diaspora community in the United Kingdom, of which he is a member. The two-fold methodological application results in an innovative and stimulating reading of the book. Overall, the book reflects a deep awareness not only of issues surrounding Esther but of the broader fields of the study of the Bible and of the ancient Near East.